ANTHROPOLOGICAL COMPREHENSION OF A WOMAN-AUTHOR AS THE SUBJECT OF CULTURE THROUGH THE PRISM OF LANGUAGE AND LITERATURE (GENDER ASPECT) - I. A. Koliieva; T. A. Kuptsova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To study the phenomenon of a woman-author as a subject of culture and philosophy from a development of literary aspect in the works both Western and Ukrainian scientists. To define the significance of the philosophical representation of the gender stereotypes to reconsider their place and role in the socio cultural discourse. Theoretical basis. To investigate the theoretical framework in the postmodern philosophy the cross-disciplinary approach is used. The comparative approach is methodologically important to clarify the problems concerning a woman-author as a subject of culture. It is underlined that the boundary line between literature and philosophy is movable, which coincides with the shapes of the human experience. Based on the conviction that gender has integrated into all social relations, that means it is a gender context of any social interaction, it is important to emphasize the productivity of a new scientific methodology of sociocultural constructing of gender. Originality. Is in systematic literary analysis of Ukrainian and Western women’s prose as specific philosophical phenomenon. It was proved that the investigation of women’s literature, its identity is an important focus of both philosophy and culture, which helps find philosophical problems in literary texts. Besides the analysis of gender implications in texts allows to start theoretical dialogue on gender problems, which means the participation in the discussion about the targets of our cultural life. Conclusions. It has been proved that literature of the ХХth-XXIst centuries is characterized by strengthening interaction between philosophical systems and literary works that reflects mainstreaming of intellectual and thinking bases. It was revealed that women’s philosophical and literary conceptions have created a unique woman’s world of being and an image of "a new woman", thus leading the way towards the new stereotypes based on comprehension that sex differences should not be determining factors both in cultural and social coexistence.